Institutional Investment in Housing: Financialisation 2.0 in the Case of Ireland - Daly, Pierce (Statistical and Social Inquiry Society of Ireland, 2023)
This paper examines the growth of institutional housing investment in Ireland, part of a global phenomenon known as “Financialisation 2.0”. Using a unique Institutional Investment Database (IID) produced specifically for this study, I present the most granular assessment of institutional investment in Irish housing to date. While institutional investors represent an important source of capital for housing development, results suggest their role in supporting new supply is more nuanced than previously suggested. Between 2012 and 2018, institutional investors primarily acquired second-hand units, with investment in new housing only dominating since 2020. Moreover, when new housing purchases by investors that receive public-financing are excluded, along with new units purchased from major Irish home-builders, the role of solely private funded investors in supporting new supply appears less significant. This highlights the need to distinguish between Irish home-builders and institutional investors in national statistics on housing supply, given differences in their business models. Separately, results present new detail on the location, type and names of this concentrated group of investors. As well as the evolving role of different investors over time. The concentration of institutional investment in Dublin (and within specific postcodes), including its growing share of (1) residential property transactions, and (2) the private rental stock, suggests this investment may have the potential to impact on house price and rent dynamics. These results highlight the need for further research on benefits and costs of institutional investment.
Barrington Lecture 2022/23 (read before the Society, 26th January 2023)
Keywords: Financialization 2.0; Institutional Investors; REIFs; REITs; Housing Supply; House Prices; Rents; 314.15